Recommendations for photoprotection of parenteral nutrition for premature infants: An ASPEN position paper. (1st September 2021) - Robinson, Daniel T.; Ayers, Phil; Fleming, Barbara; Gura, Kathleen M.; Gutsul, Liliia; Michalski, Austin; Holcombe, Beverly; Sacks, Gordon S.
Abstract: Although crucial in improving health outcomes in the preterm infants, parenteral nutrition (PN) is not without risk, especially if handled improperly. A growing body of evidence suggests that components of PN admixtures, including lipid injectable emulsions (ILEs), are susceptible to degradation, including oxidation when exposed to light (ie, photo‐oxidation), resulting in the production of reactive oxygen species. Infants, especially those born preterm, are considered more susceptible to consequences of oxidative stress than children and adults. Oxidative stress is associated with bronchopulmonary dysplasia, retinopathy of prematurity, necrotizing enterocolitis, and intestinal failure–associated liver disease. The American Society for Parenteral and Enteral Nutrition (ASPEN) assembled a working group to provide recommendations on clinical practice surrounding photoprotection of PN.This Position Paper reviews the scientific literature on the formation of quantifiable peroxides and other degradation products when PN admixtures and ILEs are exposed to light and reports adverse clinical outcomes in premature infants exposed to PN. Recommendations for photoprotection of PN admixtures and ILEs are provided, as well as the challenges in achieving complete photoprotection with the equipment, supplies, and materials currently available in the US. ASPEN and the authors understand that the full implementation of complete photoprotection may not currently be feasible given current product availability; recommendations provided in this paper serve to represent the goal to which to strive as well as to highlight the importance of product availability to achieve these practices. This paper has been approved by the ASPEN Board of Directors.